Epitaxial facet junctions on TiO2 single crystals for efficient photocatalytic water splitting - Ai-Yong, Zhang; Wei-Yi, Wang; Jie-Jie Chen; Liu, Chang; Li, Qun-Xiang; Zhang, Xing; Wen-Wei, Li; Yang, Si; Han-Qing, Yu (Energy & environmental science, 2018)
Metal oxide semiconductors with surface homojunctions characteristic of continuous band bending and well-defined epitaxial interfaces show amazing potential for photocatalytic applications. Herein, a new concept of facet junctions is proposed and validated according to the synergy between the co-exposed crystal facets of shape-tailored anatase TiO2 single crystals. By considering the atomic and electronic interactions between the co-exposed facets, our density functional theory calculations reveal the existence of type-II band alignment between the co-exposed {001} and {101} facets. This band alignment results in in situ construction of a facet junction to allow built-in facet-mediated carrier transfer. The self-constructed {101}/{001} facet junction, due to the effective carrier separation between different exposed facets, exhibits a significantly enhanced quantum efficiency and catalytic performance in photochemical hydrogen generation compared to TiO2 poly-crystals. These findings open a new horizon of facet junction-engineered nano-catalysts for more robust and efficient energy and environmental applications.